REALIGNMENT OF LANGUAGE INSTRUCTION AND DIGITAL PEDAGOGY IN TEACHER DEVELOPMENT PROGRAMMES IN EKITI STATE, NIGERIA - Faloye, Bankole; Oladunni Olufunso Deji-Afuye, (JOEL: Journal of Educational and Language Research, 2023)
This study attempted an assessment of the language and digital pedagogy of teacher development programmes in Southwest Nigeria universities. To achieve this purpose, four research questions were raised to guide the study. This study utilised the descriptive research design. The sample for this study comprised 33 full-time lecturers in the Department of Language Education in three government-owned universities in Ekiti state. The Digital Pedagogy and Language Instruction Repertoire Questionnaire (DPLIRQ) was employed for data retrieval. The correlation coefficient yielded an internal consistency of 0.84, adjudged high enough for the study. Data were collected by the researcher and analysed using descriptive and inferential statistical methods with weighted means and standard deviation. The result showed an appreciable level of lecturers’ digital awareness and pedagogical proficiency in language instruction. However, the result also showed insufficient and under-utilization of state-of-the-art digital tools for language instruction in Southwest Nigerian universities. Generally, the results of this study showed the need to fully inculcate digital pedagogy in language education programmes in the curriculum of government-owned universities in Southwest Nigeria. Based on the findings, the study encapsulated recommendations for adequate provision of state–of–the–art digital facilities in language education programmes in the university system.